Tax Aggressiveness, Debt Maturity Structure, and Firm Performance in Indonesian Real Estate Firms: The Moderating Role of Audit Quality - Nurwita Nurwita (Goodwood Publishing, 2025)
Purpose: This study examines whether tax aggressiveness and debt maturity structure affect firm performance in Indonesia’s listed real estate and property companies, and whether audit quality can reduce the negative impact of tax aggressiveness, especially when refinancing pressure is high. Research Methodology: The study focuses on real estate and property firms listed on the Indonesia Stock Exchange (IDX), The analysis can be implemented in Stata or equivalent econometric software. Results: The findings indicate that firm performance is persistent over time. Tax aggressiveness shows a nonlinear (inverted-U) relationship with performance: moderate tax aggressiveness is associated with higher profitability, while excessive tax aggressiveness reduces performance. A higher short-term debt ratio is negatively related to firm performance. Conclusions: Tax strategies in Indonesian real estate firms cannot be evaluated in isolation. Moderate tax aggressiveness may support performance through cash savings, but excessive aggressiveness can destroy value when uncertainty and information risk increase. Firms with high refinancing pressure face stronger downside effects from aggressive tax behavior.. Limitations: The study relies on archival proxies (e.g., CETR for tax aggressiveness and Big 4 affiliation for audit quality), which may not fully capture managerial intent or the full spectrum of audit effectiveness Contribution: This study contributes to corporate finance, accounting, and governance research by integrating tax behavior, debt maturity risk, and audit quality within a dynamic panel framework in an emerging-market setting.